2009
DOI: 10.1152/ajpregu.00119.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral adaptations to chronic anemia in a model of erythropoietin-deficient mice exposed to hypoxia

Abstract: Anemia and hypoxia in rats result in an increase in factors potentially involved in cerebral angiogenesis. Therefore, the aim of this study was to assess the effect of chronic anemia and/or chronic hypoxia on cerebral cellular responses and angiogenesis in wild-type and anemic transgenic mice. These studies were done in erythropoietin-deficient mice (Epo-TAg(h)) in normoxia and following acute (one day) and chronic (14 days, barometric pressure = 420 mmHg) hypoxia. In normoxia, Epo-TAg(h) mice showed an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 61 publications
(88 reference statements)
2
38
0
4
Order By: Relevance
“…The physiologic role of nNOS and regulation of pVHL/HIF in chronic anemia needs to be addressed (41). In the setting of chronic anemia, changes in SNO bioavailability and S-nitrosothiol signaling may affect angiogenesis as demonstrated in a model of myocardial ischemia (30).…”
Section: Discussionmentioning
confidence: 99%
“…The physiologic role of nNOS and regulation of pVHL/HIF in chronic anemia needs to be addressed (41). In the setting of chronic anemia, changes in SNO bioavailability and S-nitrosothiol signaling may affect angiogenesis as demonstrated in a model of myocardial ischemia (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of these responses, healthy young mice experience a shift in their mean lethal Hb concentration from 25 gÁL -1 to a higher value near 35 gÁL -1 . 21 Experimental models have shown that these hypoxic cellular responses are also upregulated during chronic anemia 27 and in older hypertensive rodents, 28 suggesting that they may have relevance to both the pediatric and the older adult patient populations that undergo anesthesia for surgical treatment. The overall conclusion from current experimental models strongly suggests that impaired oxygen delivery and tissue hypoxia contribute to increased mortality during acute anemia.…”
Section: Why Is Anemia Unsafe?mentioning
confidence: 99%
“…[33][34][35] Our previous studies have demonstrated evidence of increased vascular endothelial growth factor (VEGF) RNA and protein in brain homogenates from anemic rats, suggesting that angiogenesis may be acutely activated. The current microarray data demonstrated that angiopoietin 2 (angiogenic factor) increased progressively after 6 and 24 hr of anemia.…”
Section: Genes Involved In Angiogenesismentioning
confidence: 99%